Pengaruh Komitmen Organisasi, Personal Cost, Dan Tingkat Keseriusan Kecurangan Terhadap Intention Whistleblowing - Marwan Daud, Mayang; Tumirin (Akmenika: Jurnal Akuntansi dan Manajemen, 2024)
The purpose of this study is to examine how organizational commitment, personal cost, and the severity of the situation influence the willingness to report violations. This quantitative research involved 74 civil servants employed by regional organizations. A questionnaire using a purposive sampling technique was used to collect data. The SmartPLS version 3 application is used for data processing. The research results show that although organizational commitment and personal cost do not have a significant effect on whistleblowing intentions, the seriousness of the incident has a significant effect on these intentions.